Roadblocks and successes in preparing COVID-19 vaccination clinics: Perspectives from pharmacy residents. (6th September 2021) - Ezeude, Ginikannwa I; Glover, Kristen R; Nieves Santiago, Alejandro A; Repella, Emily; Tang, Emily
Abstract: Purpose: To outline logistics challenges, barriers, and successes in the development of separate programs for mass COVID-19 vaccine distribution and administration to healthcare employees and community members. Summary: In the face of the global coronavirus disease 2019 (COVID-19) pandemic, COVID-19 vaccine development and distribution became a worldwide priority. AdventHealth Orlando was selected as the central hub for vaccination efforts for central Florida. There was a need to quickly evaluate literature, patient safety, and institutional resources and logistics to coordinate the development of employee and community vaccination clinics. These efforts were driven by postgraduate year 2 residents in health-system pharmacy administration and leadership, medication-use safety and policy, and informatics. Clinic development focused on 4 key areas: vaccine quality control, secure inventory movement, safe preparation and administration, and consolidation of inventory. Healthcare worker vaccinations were administered on the health system's main campus, and community vaccination events were carried out at temporary clinic facilities set up in the parking lot of Orlando International Airport. Conclusion: In a mass COVID-19 vaccination initiative directed by the pharmacy enterprise leadership of a large Florida health system, postgraduate year 2 pharmacy residents played a key role in developing and implementing vaccination clinics targeting healthcare worker and community populations. During multiple vaccination events, a total of more than 50, 000 COVID-19 vaccine doses were administered, with minimal to no vaccine wastage.